The 2018 Health Equity and Financial Protection Indicators Database : Overview and Insights - Wagstaff, Adam (World Bank, Washington, DC, 2018)
The 2018 database on Health Equity and Financial Protection indicators provides data on equity in the delivery of health service interventions and health outcomes, and on financial protection in health. This paper provides a brief history of the database, gives an overview of the contents of the 2018 version of the database, and then gets into the details of the construction of its two sides -- the health equity side and the financial protection side. The paper also provides illustrative uses of the database, including the extent of and trends in inequity in maternal and child health intervention coverage, the extent of inequities in women's cancer screening and inpatient care utilization, and trends and inequalities in the incidence of catastrophic health expenditures.